PENINGKATAN EFISIENSI DAN PERLUASAN PASAR NIRANTA GULA AREN KOTA PADANG MELALUI DIGITALISASI PEMASARAN DAN KEUANGAN - Komalasari, Sanda Patrisia; Tri, Diwah Ganda; Hadelina, Rizka; Mardiah, Ainul; Irwan, Naufal Rafif; Fadhilah, Rifa; Gumala, Azhoma; Fauzana, Annisa; Rahman, Khalilul (Jurnal Hilirisasi IPTEKS, 2025)
Micro, Small, and Medium Enterprises (MSMEs), specifically Niranta Palm Sugar in Padang City, hold immense potential but face significant challenges due to manual financial management and conventional marketing strategies. These limitations hinder operational efficiency and market expansion. This community service project aimed to enhance the efficiency and market reach of Niranta by adopting digital tools for marketing and finance. A qualitative approach with an intensive mentorship method was implemented, starting with a needs analysis, followed by financial management training using the SIAPIK application, and the development of digital marketing infrastructure, including a website, a Shopee account, and an Instagram profile. The program yielded measurable positive impacts. In finance, although the operational implementation was delegated, the partner successfully adopted a more structured digital recording system, demonstrating increased awareness of the importance of good financial governance. In marketing, the new digital infrastructure effectively broadened the market reach. The company’s website recorded 607 visitors in the first month, and the Shopee account successfully gained followers and initiated sales transactions. While a significant increase in sales is not yet apparent as the program is in its early stages, it has successfully opened new markets. Overall, the digitalization of marketing and finance has proven effective in substantially boosting the competitiveness of Niranta Palm Sugar MSME, demonstrating that technology-focused mentorship can have a tangible impact on the growth of MSME businesses.